Polyfunctional type-1, -2, and -17 CD8⁺ T cell responses to apoptotic self-antigens correlate with the chronic evolution of hepatitis C virus infection. - Debora Franceschini; Paola Del Porto; Silvia Piconese; Emanuele Trella; Daniele Accapezzato; Marino Paroli; Stefania Morrone; Enza Piccolella; Enea Spada; Alfonso Mele; John Sidney; Alessandro Sette; et al. (PLoS Pathogens, 2012)
Caspase-dependent cleavage of antigens associated with apoptotic cells plays a prominent role in the generation of CD8⁺ T cell responses in various infectious diseases. We found that the emergence of a large population of autoreactive CD8⁺ T effector cells specific for apoptotic T cell-associated self-epitopes exceeds the antiviral responses in patients with acute hepatitis C virus infection. Importantly, they endow mixed polyfunctional type-1, type-2 and type-17 responses and correlate with the chronic progression of infection. This evolution is related to the selection of autoreactive CD8⁺ T cells with higher T cell receptor avidity, whereas those with lower avidity undergo prompt contraction in patients who clear infection. These findings demonstrate a previously undescribed strict link between the emergence of high frequencies of mixed autoreactive CD8⁺ T cells producing a broad array of cytokines (IFN-γ, IL-17, IL-4, IL-2…) and the progression toward chronic disease in a human model of acute infection.